Tinjauan Yuridis Pelaksanaan Perjanjian Penitipan Anak Di Panti Asuhan Kristen Gmit 221 Kupang - Adoe, Diego Marco; Hedewata, Agustinus; Dinata, Husni Kusuma (Artemis Law Journal, 2024)
The rights and obligations that must be carried out by the parties in carrying out child care at the GMIT 221 Christian orphanage in Kupang. The parents have the right to be guaranteed that the child will be cared for and maintained properly and lovingly and are obliged to fulfill the requirements for registration and submission of children to the GMIT 221 Kupang Christian Orphanage and are ready to accept the child back when the child care by the orphanage has ended, or the child care is terminated by the orphanage. The main problems in this thesis are: (1) How is the implementation of the child care agreement carried out at the GMIT 221 Kupang Christian Orphanage? (2) What are the rights and obligations of each party that must be bound in the care agreement at the GMIT 221 Kupang Christian Orphanage? The conclusions of this research are: (1) the implementation of the child care agreement is carried out with the introduction stage and continued with the agreement implementation stage. (2) The rights and obligations of the parties to the child care agreement must be cooperative and committed to the agreement that has been made. Based on this research, the researcher suggests that orphanages should expand relationships with outside parties so that orphanages can more easily get help both in labor and material and orphanages should pay more attention to the rights and obligations of children who will be entrusted or submitted to orphanages.